Characterization and Comparative Analysis of RWP-RK Proteins from Arachis duranensis, Arachis ipaensis, and Arachis hypogaea - Chenyang Liu; Dongliang Yuan; Tong Liu; Mengge Xing; Wenying Xu; Huiying Zhang; Hanqi Jin; Chunmei Cai; Shuai Li (International Journal of Genomics)
RWP-RK proteins are important factors involved in nitrate response and gametophyte development in plants, and the functions of RWP-RK proteins have been analyzed in many species. However, the characterization of peanut RWP-RK proteins is limited. In this study, we identified 16, 19, and 32 RWP-RK members from Arachis duranensis, Arachis ipaensis, and Arachis hypogaea, respectively, and investigated their evolution relationships. The RWP-RK proteins were classified into two groups, RWP-RK domain proteins and NODULE-INCEPTION-like proteins. Chromosomal distributions, gene structures, and conserved motifs of RWP-RK genes were compared among wild and cultivated peanuts. In addition, we identified 12 orthologous gene pairs from the two wild peanut species, 13 from A. duranensis and A. hypogaea, and 13 from A. ipaensis and A. hypogaea. One, one, and seventeen duplicated gene pairs were identified within the A. duranensis, A. ipaensis, and A. hypogaea genomes, respectively. Moreover, different numbers of cis-acting elements in the RWP-RK promoters were found in wild and cultivated species (87 in A. duranensis, 89 in A. ipaensis, and 92 in A. hypogaea), and as a result, many RWP-RK genes showed distinct expression patterns in different tissues. Our study will provide useful information for further functional and evolutionary analysis of the RWP-RK genes.